K2CO3-Activated Pomelo Peels as a High-Performance Adsorbent for Removal of Cu(II): Preparation, Characterization, and Adsorption Studies - Zheng Liu; Yuling Wei (Journal of Chemistry)
Activated carbons (ACs) were prepared from pomelo peels by K2CO3 activation and used as an adsorbent (PAC) for the removal of Cu(II) from aqueous solutions. BET, SEM, and FT-IR were employed for the characterization of the obtained ACs. The optimum ACs were reported at activation temperature of 850°C, activation time of 60 min, and impregnation ratio of 3, which had a high surface area (1213 m2/g) and total pore volume (0.57 cm3/g). The resulting ACs were used for the adsorption of Cu(II) from aqueous solutions in the batch mode and yielded a superior adsorption capacity of 139.08 mg/g. The pH of optimum adsorption was determined as 5. Pseudo first-order model, pseudo second-order model, and intraparticle diffusion model were applied to describe the adsorption processes. The adsorption kinetic data were found to follow the pseudo second-order model. The adsorption isotherms data were analyzed using Langmuir, Freundlich, Temkin, and Dubinin–Radushkevich models. The Langmuir model was found to provide the best fit, and the calculated adsorption capacity was 151.35 mg/g.